Women Entrepreneurial Inclusiveness And Performance: Perspective From Non-Oil Export In Lagos State, Nigeria - Oluwatoyin ADESANYA; Chinonye MOSES; Rowland WORLU; Olaleke OGUNNAIKE; Olufunke ADEBAYO; Aloysius ISOWEDE (Communications of International Proceedings, 2020)
Women entrepreneurship is an inclusive entrepreneurial activity of women who initiates businesses with potential for innovation and competitiveness. Women contribution both in domestic and international trade is significantly essential to the overall economy and for improved national GDP. The assumption is that women entrepreneurs' contribution to export is critical to achieving SDG plans 1 -5, 10 and 12- zero hunger, good health and wellbeing, gender equality, quality education, poverty reduction and responsible consumption and production. However, women entrepreneurs face limitations ranging from the initial start-up fund, socio-cultural, political, legal and environmental problems, governmental inconsistencies, operational infrastructure constraints. These evolved low intensity of entrepreneurial involvement, and many women are establishing their businesses in the low-growth informal sector, thereby hindering sustainable growth in the nation. Hence the focus of the study is to measure the relationship between women entrepreneurial inclusiveness and the inherent constraints in the non-oil export sector and the performance implication.  The study adopted a descriptive approach using SPSS version 24 via both correlational and regression data analyses. The study employed one hundred and thirty-four (134) women entrepreneurs in Spice and Food processing, Apparel/Fashion, and Information Technology services as sample population for the survey. The findings indicated governmental policy inconsistent and support constraint have an inverse relationship with women entrepreneurs' performance, explaining it as a critical issue, while procedural, and environmental have a moderate effect, marketing constraint has no significant effect. Hence, women entrepreneurs need improved government support, favourable policies, and entrepreneurial training required for sustainable higher innovative performance in the export market.
Keywords: Women entrepreneurial inclusiveness; Entrepreneurial Constrains; Non-Oil Export; Performance.